Efektivitas FIFA 11+ untuk Peningkatan Kelincahan dan Keseimbangan pada Pemain Sepak Bola: Literature Review - Lestari, Sulis; Rahayu, Umi Budi; Wijianto; Sari, Dwi Rosella Komala (MAN Insan Cendekia Jambi, 2025)
FIFA 11+ is a structured warm-up program developed by the FIFA Medical and Research Center (F-MARC) to prevent injuries and enhance physical performance in football players. This literature review aims to analyze the effectiveness of FIFA 11+ in improving agility and balance in football players. The study applied a literature review method using scientific databases such as Google Scholar, PubMed, and ScienceDirect. Findings from eleven reviewed articles consistently indicate that FIFA 11+ significantly improves dynamic balance and agility, while also contributing to the reduction of injury risk, particularly in the lower extremities. The program has proven effective across various age groups, both amateur and professional players, and is suitable for daily warm-up routines to support performance and prevent injuries.